Stayers in China's “hollowed‐out” villages: A counter narrative on massive rural–urban migration - Ye, Jingzhong (Population space and place, 2018)
China has been undergoing a rapid industrialisation and urbanisation process with an ongoing transfer of people and economic resources from rural to urban areas. Labour migration from rural to urban areas has been massive and become a “rite of passage” for rural young people. There is a widespread view that modernisation and the subsequent transformation of peasants, agriculture, and the countryside have undermined agriculture and hollowed out rural communities. However, due to the peculiarity of the hukou system and the circularity of rural urban migration, the large rural population can all be institutionally regarded as de jure rural stayers. The de facto rural stayers consist of the left‐behind ones and the non‐left‐behind ones. Yet these categories are quite fluid links with migration as people make different decisions at different stage in their life cycle. Motivations for migrating and staying in the countryside are highly complex. Those who migrate often do so because of economic pushes resulting from the commodification of subsistence. Many women who stay behind do so because of structural forces, such as the traditional culture of gender division and economic coercion. The non‐left‐behind people who are not stuck in the countryside are often able to actively pursue alternative rural livelihoods. These rural stayers develop diversified livelihood strategies that involve multiple job holding and make significant contributions to their household livelihoods and to driving rural development. The paper concludes that rural villages are not, as is often supposed, hollowed out, and many rural stayers do so voluntarily.